(untitled) (Global Journal of Human-Social Science, 2023)
The article deals with global law and the duties of the State Transnational legal production is a current and challenging phenomenon If it brings benefits it can bring dangers especially to States requiring behavior consistent with the current situation The article questions what are the dangers of global law and what duties do States have in this context The general objective is to identify the dangers arising from global law and to verify what are the duties of States within a scenario of transnational legal production Among the specific objectives the first one addressed in the first topic is to study what global law is Then in the second topic the problems arising from the idea of global law is identified Finally in the final part it is verified what are the duties of the States in this context It was possible to conclude that it is the duty of the States to have an active posture in this process of transnational legal production acting in the regulation and control of this legal production so that the dangers arising from it do not materialize in the reality of society The study was developed from a bibliographic research under the hypothetical-deductive method KEYWORDS Global law Democracy Duties State